You've done something wrong. Not sure what it is, but this is how I did it
(x-1)/(x+4) = (x+3)/(x-7)
(x-1)/(x+4) - (x+3)/(x-7) = 0
((x-1)(x-7) - (x+4)(x+3)) / ((x+4)(x-7)) = 0
(x-1)/(x-7) - (x+4)/(x+3) = 0
x^2 - 8x + 7 - (x^2 + 7x + 12) = 0
-15x - 5 = 0
-15x = 5
x = -5/15 = -1/3
Line 5 is written incorrectly, but as line 6 is correct I suspect it's just a typo. Both your and Soroban's derivations are correct, you simply used a slightly different method.
Line 5 is written incorrectly, but as line 6 is correct I suspect it's just a typo. Both your and Soroban's derivations are correct, you simply used a slightly different method.
-Dan
Oops, typo. Theres not supposed to be '/' in there